Smart Interaction of Object on Internet of Things - Kujur, Pranay; Gautam, Kiran (International Journal of Computer Sciences and Engineering, 2015)
The Internet of Things (IOT) is a scenario in which objects, animals or people are provided with unique identifiers and the ability to sense analyses and transfer data over a network without requiring human-to-things interaction. IOT has evolved from the convergence of wireless technologies, micro-electromechanical systems and the Internet. Various scenario in which human-physical objects interaction and physical object-physical object interaction can be predicted with the help of past temporal information. IOT provide flow of information whenever a things are interacting with other things and human as well. A physical thing like RFID is implanted with its unique address using private and public network which is known to the end user. Based on the evaluation of temporal information human behavior is studied for particular thing of interest and things on the other hand could interact with the end user.